Liberability : A new approach for measuring ore comminution behavior - Mwanga, Abdul; Lamberg, Pertti; Rosenkranz, Jan (Luleå tekniska universitet, Mineralteknik och metallurgi, 2014)
Crushability and grindability are traditionally used to describe the material properties in comminution. These parameters neglect the main objective of ore comminution, the mineral liberation and therefore information is incomplete. A new concept called liberability: the easiness of mineral liberation in comminution is introduced to fill the gap. Establishing a liberability map of a deposit requires grindability tests and liberation measurements for the grinding product. The liberability curve shows the degree of liberation of the mineral against grinding energy and offers better baseline for resource optimization than the grindability curve. A case study with a magnetite iron ore from Malmberget, northern Sweden, shows that certain shortcuts can be applied to keep the experimental effort reasonable which is important, particularly when applying the liberability in a geometallurgical program. In Malmberget the liberability is depending on the grade and grain size of magnetite. A significant difference between grindability and liberability can be observed. Godkänd; 2014; 20141122 (abdmwa)